(untitled) (Journal of Pure and Applied Sciences (Science Forum), 2026)
Soil samples collected from some farmlands very close to municipal dumpsites located in Jos, Plateau state, were studied to assess the soil quality of the farms with respect to the soil physicochemical properties and heavy metal concentration. The results show that the soil samples from the farm and control sites are loamy, while that from the dumpsites are sandy (containing sand fraction >85.0%). Soil mean pH varied between 5.902 ± 0.02 in Zaria road control soil and 7.16 ± 0.22 in Zaria road farm. While the cation exchange capacity (cmol kg−1) in the farm soils (14.35 ± 0.66, 12.44 ± 0.20) are higher than that of the control sites (8.35 ± 0.75, 7.41 ± 0.10) and consistent with the dumpsites (23.60 ± 0.02, 21.18 ± 0.01), the percentage organic matter in all the study sites is far above the average level by FAO for agricultural soil. The concentrations of all the metals (Zn, Co, Cr, Pb, As, Cd, and Cu) in the dumpsites and farm soil are higher than those of the control, permissible limits of the WHO, EU, and the Department of Petroleum Resources target for metals, except Cd, Zn, Co, Pb, and Cu were predominant in the sites, while As and Cd had low concentrations. With the exception of Zn and Cr in the farm soils, all the heavy metals had anthropogenic inputs of >50%. The index of geoaccumulation results for the metals showed moderate pollution of the farm soils with Cr, Pb, As, Co, and Zn, and a strong pol lution with respect to Cd. The continuous dumping of waste in these areas may, therefore, constitute a serious threat to the soil qualities of nearby farms.